2022
DOI: 10.3390/ma15248992
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation Resistance and Pore Structure of Mixed-Fiber-Reinforced Concrete Containing Fine Aggregates of Iron Ore Tailings

Abstract: The disposal of industrial by-product tailings has become an important issue in solving environmental pollution. In this study, 15%, 30%, 50%, and 70% iron tailings were used to replace the natural sand in concrete, and 1.5% steel fiber and 0–0.75% PVA fibers were added to the iron tailings concrete. The effects of the iron tailings replacement rate and the fiber content on the mechanical properties, carbonization depth, and concrete porosity were studied in a carbonization environment. The results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…Based on the slower growth rate of the experimental data, the best fit was chosen at b = 0.5. The correlation is significant, with R 2 = 0.51, which is consistent with previous findings in Zheng [67], Zheng [68] and Wang [26]. This implies that the change rule of all of the NZS 3101 [69] 0.44 × (f UCS ) 0.5 NZS 3101 [69] 0.60 × (f UCS ) 0.5 EC-04 [70] 0.30 × (f UCS ) (2/3) EC 04 [70] 0.435 × (f UCS ) (2/3) GB 50010 [71] 0.19 × (f UCS ) 0.75 DG/TJ [72] 0.75 × (f UCS ) 0.5 JSCE [73] 0…”
Section: Flexural Strength (Fs)supporting
confidence: 91%
See 2 more Smart Citations
“…Based on the slower growth rate of the experimental data, the best fit was chosen at b = 0.5. The correlation is significant, with R 2 = 0.51, which is consistent with previous findings in Zheng [67], Zheng [68] and Wang [26]. This implies that the change rule of all of the NZS 3101 [69] 0.44 × (f UCS ) 0.5 NZS 3101 [69] 0.60 × (f UCS ) 0.5 EC-04 [70] 0.30 × (f UCS ) (2/3) EC 04 [70] 0.435 × (f UCS ) (2/3) GB 50010 [71] 0.19 × (f UCS ) 0.75 DG/TJ [72] 0.75 × (f UCS ) 0.5 JSCE [73] 0…”
Section: Flexural Strength (Fs)supporting
confidence: 91%
“…Based on the slower growth rate of the experimental data, the best fit was chosen at b = 0.5. The correlation is significant, with R 2 = 0.51, which is consistent with previous findings in Zheng [67], Zheng [68] and Wang [26]. This implies that the change rule of all of the strength indexes is similar for the fiber types and contents, and the best fiber combination is B0.25P0.05.…”
Section: Flexural Strength (Fs)supporting
confidence: 89%
See 1 more Smart Citation
“…Research has demonstrated that the incorporation of fibers [21,22] into the filling process can effectively retard the degradation of the filling material [23,24]. Moreover, the bridging effect of fibers within the filling material [25][26][27] significantly enhances the mechanical properties of the cemented filling [28,29]. Following laboratory tests, Li [30] concluded that the unconfined compressive strength of fiber-reinforced cemented tailings backfill (FRCTB) increased with the increase in polypropylene (PP) fiber dosage, and the peak strain also increased from 0.39% to 1.45%.…”
Section: Introductionmentioning
confidence: 99%
“…[15] aim to identify the influence of the incorporation of iron ore tailings (IOT) obtained from the Germano dam in Brazil in the substitution of sand fractions in concrete. 15%, 30%, 50%, and 70% iron tailings were used to replace the natural sand in concrete, and 1.5% steel fiber and 0-0.75% PVA fibers were added to the iron tailings concrete [16]. Other influential work includes [17].…”
Section: Introductionmentioning
confidence: 99%